Multifaceted characteristics of aridity changes and causal mechanisms in Chinese drylands. (June 2023) - Hu, Ying; Wei, Fangli; Fu, Bojie; Wang, Shuai; Wang, Lanhui; Chen, Yongzhe
The water cycle is accelerating in the context of global warming. However, how the multifaceted characteristics of aridity, particularly atmospheric, hydrological, and ecological drying, change and interact with each other are largely unknown. A gap we bridged was discovering the causal relationships underlying the atmosphere-hydrosphere-biosphere nexus from the nonlinear dynamic system perspective based on convergent cross mapping (CCM). Dryland area in China has expanded since 1982, while the vegetation greenness indicated by leaf area index has been increasing during the same period. The results showed that the causality among atmospheric, hydrological, and ecological drying in different subtypes of drylands was different. In arid and semi-arid regions: vegetation changes were mainly driven by soil moisture (SM) and vapor pressure deficit (VPD), and VPD regulated SM. In hyper-arid and dry sub-humid areas: VPD dominated vegetation changes. VPD increases did not contribute to SM loss under the intense water stress in hyper-arid regions, as the soil water supply cannot meet the atmospheric water demand. In dry sub-humid areas, human disturbances have attenuated the dependence of vegetation changes on SM variability. This research pioneers complex nonlinear dynamic analyses on the multifaceted characteristics of ecosystems, which can deepen our understanding of atmosphere-vegetation-soil interactions in drylands and guide the sustainable management of dryland ecosystems in China and elsewhere. Graphical Abstract